Comparative Analysis of Post Rubber Band Ligation and Stapled Hemorrhoidopexy Complications of Grade 2 and 3 Internal Hemorrhoids - Mazni, Yarman; Basir, Ibrahim; Sumanto, Sumanto; Budiningsih, Setyawati (UI Scholars Hub, 2018)
Introduction. The management of second–and third–degree internal hemorrhoid consists of non–surgical and surgical treatments. If non–surgical treatment does not succeed, then the recommended therapy is minimal invasive or surgery, depends on the clinical condition. Along with the development of science and technology, a technique known as rubber band ligation (RBL) and stapled hemorrhoidopexy emerges. In Indonesia, there is no data that can describe the distribution of postoperative complication rate. Method. A comparative cross–sectional study was conducted by gathering short term outcomes data from the subjects' medical records that underwent RBL or SH between 2011 to 2014 in three different hospitals in Jakarta. A univariate analysis was conducted to assess postoperative complications of RBL and SH subjects of second–and third–degree internal hemorrhoids. We use chi square test to assess the factors that influence the complications of categorical variables, and Fisher test if the chi square condition is not met. Results. Among 183 subjects, 49.2% underwent RBL and 50.8% SH. Second degree internal hemorrhoids were 40% and third degree were 60%. Postoperative complications consist of pain (RBL 4.4%, SH 8.8%), hemorrhage (RBL 2.3%, SH 4.9%), urinary retention (RBL 0, SH 2.7%), infection (RBL 0.5%, SH 1.6%) and stenosis (RBL 0, SH 0.5%). Postoperative complications on second degree internal hemorrhoidal was 8.2% and third degree 13.1% (p = 0.71). Complication of subject with third degree internal hemorrhoids after RBL 2.8%, SH 19.4% (p = 0.03). Conclusion. Complications of second– and third–degree internal hemorrhoids post RBL are no different with SH while for third degree internal hemorrhoid, complications after RBL ware significantly lower than SH.